Realignment strategies in the US retail industry during a recessionary time. Issue 8 (10th August 2015) - Mann, Manveer; Byun, Sang-Eun; Li, Yishuang
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the range of realignment strategies employed by retailers in the USA in response to the 2008 economic recession. Design/methodology/approach – Following the grounded theory approach, National Retail Federation News Briefs published between 2008 and 2011 were analyzed by sorting them into thematic categories and comparing trends in strategic decisions during the recession (2008-2009) and after the recession (2010-2011). Based on the emergent categories, propositions were developed to provide theoretical explanations of the findings. Findings – The authors found five thematic categories of realignment strategies: promotional, organizational, price, operational, and product realignments. In line with contingency theories, retailers used these strategies to achieve a greater fit with the altered business environment and consumer consumption patterns. While promotional realignment was most prevalent, followed by organizational realignment, different realignment strategies were pursued based on the strategic focus and long-term vs short-term orientation of the retailers. Originality/value – The contribution of the findings is twofold: filling a critical gap in the literature examining the range of realignment decisions of the US retail industry in response to the recent economic recession; and enhancing the theoretical understanding of underlying factors or mechanisms of specific realignment decisions in the context of a turbulent economic environment.